2024
DOI: 10.1001/jamanetworkopen.2023.50950
|View full text |Cite
|
Sign up to set email alerts
|

Fat Body Mass and Vertebral Fracture Progression in Women With Breast Cancer

Deborah Cosentini,
Rebecca Pedersini,
Pierluigi Di Mauro
et al.

Abstract: ImportanceWomen with early breast cancer (EBC) exposed to aromatase inhibitors (AIs) may experience fragility fractures despite treatment with bone-active drugs. Risk factors for fractures in patients receiving AIs and denosumab have not been explored to date.ObjectivesTo evaluate whether an association exists between dual x-ray absorptiometry (DXA)–measured fat body mass (FBM) and vertebral fracture (VF) progression in postmenopausal women with EBC undergoing adjuvant therapy with AIs in combination with deno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This condition is notoriously associated with a general increase in patient fragility, leading to increased risks of mobility impairment, disability, lower quality of life, and allcause mortality Sarcopenic obesity also places the patient at greater risk of skeletal fragility [36,37]. In a previous crosssectional study led by our group on EBC patients treated with AIs the frequency of vertebral fractures was most associated with the phenotype of low lean mass and high fat mass [37,38]. In a subsequent study FBM was found to be an independent risk factor of vertebra fracture progression after AIs.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is notoriously associated with a general increase in patient fragility, leading to increased risks of mobility impairment, disability, lower quality of life, and allcause mortality Sarcopenic obesity also places the patient at greater risk of skeletal fragility [36,37]. In a previous crosssectional study led by our group on EBC patients treated with AIs the frequency of vertebral fractures was most associated with the phenotype of low lean mass and high fat mass [37,38]. In a subsequent study FBM was found to be an independent risk factor of vertebra fracture progression after AIs.…”
Section: Discussionmentioning
confidence: 99%